Aktualisasi Masyarakat Kampung Islam Kepaon di Desa Pemogan Denpasar - Wulandari, Riza (Prodi Sosiologi Agama, 2017)
Kampung Islam Kepaon (Islamic Village Kepaon) is an example of an Islamic village. This village is located in the Pemogan area. This village is trying to retain its identity in the middle of life’s complexities of Hindu community dominance. The trace record of the village is historical evidence that still exists in the modern era. Thisresearch aims to know how the actualization of existing community in the village using Abraham Maslow's concept and Max Weber’s theory of Social Action. This research is qualitatively based research using single case studies. Observation, deep interviews, and documentation by photograph are the tools for collecting data. The selected interviewees are the chief of the village, elders, and some selected individuals based on gender and their active role. The results of this research show that the actualization of the Islamic community in the village is so powerful. There are several activities to actualize the existence of the village’s communities who live side by side with the Hindu communities such as the tradition of ngejot, the rodent tradition at Prophet Muhammad’s Maulid ceremony, mekibung, reinforcement of the Balinese language as a form of emerging Bali local wisdom, education-based Islamic, Rebana, and Bleganjur.